Visible-light activation of TiO2 by dye-sensitization for degradation of pharmaceutical compounds. Issue 4 (20th November 2018) - Diaz-Angulo, Jennyfer; Gomez-Bonilla, Islen; Jimenez-Tohapanta, Christian; Mueses, Miguel; Pinzon, Maria; Machuca-Martinez, Fiderman
Abstract : A kinetic model for the dye sensitization process of TiO2 that considered photon absorption was developed. Abstract : This work reports the improvement in the photon absorption and degradation of acetaminophen (ACF) and diclofenac (DFC) by photosensitizing TiO2 with two types of dyes Eosin Y (Ey) and Rhodamine B (RhB). Experimental tests were carried out in a solar simulator for three hours for different systems and both pollutants. The influences of the TiO2 concentration (100, 200 and 800 mg L −1 ) and the catalyst–dye ratio (2%, 5% and 10%) were investigated. The degradation of the compounds was higher in the presence of TiO2 -Ey compared to the TiO2 -RhB and TiO2 for both pharmaceutical compounds, which was attributed to the anionic nature of Ey. DFC total degradation was achieved using 100 mg L −1 of catalyst loading and 10% of catalyst–dye ratio and the highest ACF degradation (71%) was obtained at 800 mg L −1 of catalyst loading and 5% of catalyst–dye ratio. The photon absorption was studied for both dyes using the six-flux absorption scattering model (SFM) for estimating the LVRPA (local volumetric rate of photon absorption). This was done by modifying the apparent optical thickness equation. It was found that the presence of dye in the photocatalytic systems considerably increases the LVRPA. The rate coefficients for the degradation of pharmaceutical compounds in the presence of the organic dyes were also obtained.